The teaching of thinking in Malaysia - Hashim, Rosnani; Hussien, Suhailah (Research Centre, International Islamic University Malaysia, 2003)
The development of the intellectual potential and consequently the ability to think wisely has always been an important goal of education. This important landmark of an educated person is again raised today as a major issue in education, after many studies have begun to reveal symptoms of a decline in students' ability to think wisely, especially when schools began to focus on the mastery of facts, probably in the preparation for examinations rather than on the processes of arriving at those facts. The ability to think well is critical to an individual's success in life, especially in the age of Information and Communication Technology (ICT) and Globalization whereby individuals have to sieve through massive information, which might not be necessarily relevant at such a rapid pace, and the survival of industry and nation depends on competitive, knowledge capital. Should we teach thinking? Is it not a natural process and a matter of experience? After all, we were able to classify, analyze, generalize, deduce, induce, evaluate, make decisions and solve problems without any formal instructions in thinking. It is no longer true that being able to think spontaneously would lead to the ability to think effectively and wisely. Thinking could be taught and good thinking requires practice. Teachers in Malaysia are grappling with this issue in an effort to be forerunners in the country's drive to attain the status of an industrial country and a world centre of educational excellence. This work, therefore, examines the Malaysian educational policy regarding the teaching of thinking and studies that have been conducted in this area and their implications, in particular, for teacher education.